Some mechanisms of the inﬂuence of polychromatic light on the condition of the cornea, lens and retina of rabbits in the experiment - Коломійчук, Сергій Григорович (My University, 2025)
The optical system of the eye consists of the cornea and the lens and forms a “refracton” for focusing the image on the retina. Studies of the biochemi- cal and biophysical mechanisms that ensure the transparency of this sys- tem indicate the importance of the spatial arrangement of collagen ﬁbrils in the corneal stroma and crystallins in the cytoplasm of lens ﬁber cells. Post-translational modiﬁcations of proteins can lead to impaired transpar- ency and age-related cataracts (Quinlan RA, Clark JI., 2022). The structural and functional properties of eye tissues depend on metabolic processes that maintain homeostasis and adaptation of the visual analyzer to the action of pathogenic factors. One of the triggers for the development of pathological changes in eye tissues is oxidative and carbonyl stress dur- ing irradiation. Purpose: Determination of molecular mechanisms of the damaging eﬀect of polychromatic light (P L) on the condition of the cornea, lens and retina of rabbits in the experiment. Material and Methods: Chinchilla rabbits (n = 12) were irradiated with high-intensity PL daily for 23 weeks (arc mercury lamp, 350–1150 nm, 30 mW/cm2, 750 W). Control–intact animals (n = 15). The condition of the animals’ eyes was monitored by ophthalmoscopic and biomicroscopic methods. After 23 weeks, the total antioxidant ( TAA) and oxidative activ- ity ( TOA), the level of fragmented DNA (fDNA), thiol and carboxyl protein groups were determined in the tissues of the cornea, lens and retina of rabbits. Results: Previous studies have established a violation of the redox state of nicotinamide coenzymes in the tissues of the visual analyzer of rabbits un- der the inﬂuence of PL. When animals were exposed to PL, an increase in TOA was detected in the cornea by 128 %, in the lens by 137 % (p < 0.05), in the retina by 132 %, carboxyl protein groups by 126 %, 144 % and 136 % (p < 0.05) and fDNA by 124 %, 138 % and 127 % (p < 0.05), respectively, relative to the control. A statistically signiﬁcant decrease in TAA and the level of thiol protein groups in the studied tissues was established under the inﬂuence of PL. Conclusion: The data indicate that prolonged exposure to P L causes oxi- dative modiﬁcation of biopolymers associated with the processes of oxi- dative and carbonyl stress with depletion of the antioxidant system in the tissues of the eye. Correction of disorders with antioxidants will contrib- ute to the stabilization of the structural and functional properties of the visual analyzer.